Pengaruh Growth Opportunity, Net Working Capital, Cash Conversion Cycle Dan Dividend Payout Terhadap Cash Holding - Endah Ayu Wulandari; Mia Angelina Setiawan (Universitas Negeri Padang, 2019)
This study aims to determine the effect of Growth Opportunity, Net Working Capital, Cash Conversion Cycle and Dividend Payout on Cash Holding property and real estate companies listed on the Indonesia Stock Exchange. The research period used is the period 2014-2017. The design of this study is causal associative research. The sample in this study was obtained by purposive sampling method. Based on the existing criteria, 42 companies were included in the study sample. The data used is secondary data. The data analysis technique used is panel regression analysis. The results showed that Growth Opportunity and Dividend Payout had no significant effect on Cash Holding. Meanwhile, Net Working Capital and Cash Conversion Cycle have a significant effect on Cash Holding. The ability of independent variables to explain the dependent variable is 10.89% and 89.11% is explained by other variables outside of this study.